Catalytic Effect of Iron (III) Nitrate on the Synthesis of Reduced Graphene Oxide from Oil Palm Kernel Shell-Derived Graphite - Ismariza Ismail; N. A. Karim; Adilah Ayoib; Oo Cheng Hong; Muhammad M. Ramli; Shazlina Johari; Anis Syafiqa Rosman; Nurul Aishah Mohd Amran (International Journal of Nanoelectronics and Materials (IJNeaM), 2026)
This study investigates the catalytic role of iron (III) nitrate [Fe(NO₃)₃] in synthesizing reduced graphene oxide (rGO) from graphite derived from oil palm kernel shell (OPKS) biomass. OPKS was impregnated with Fe(NO₃)₃ at concentrations of 0, 10, 20, and 30 wt.% (samples G₀, G₁₀, G₂₀, and G₃₀), and were subsequently pyrolyzed for catalytic graphitization. X-ray diffraction (XRD) results showed G₂₀,which was prepared with 20 wt.% catalyst, achieved the highest degree of graphitization (97%) and a near-ideal interlayer spacing of 0.344 nm, as indicated by sharp, intense diffraction peaks. Graphite samples, G₀ and G₂₀, were oxidized via a modified Hummers’ method to obtain GO, then chemically reduced to yield rGO₀ and rGO₂₀. Raman spectroscopy, SEM, and XRD characterization confirmed that rGO₂₀ exhibited superior graphitic features compared to rGO₀, which includes a lower defect density reflected by a reduced Iᴅ/Iɢ ratio from 1.155 to 1.128, sharper XRD reflections, and larger, well- defined pores. Collectively, these results highlight the critical influence of Fe(NO₃)₃ concentration in enhancing precursor graphite crystallinity and, consequently, the structural quality of the derived rGO. Catalytic graphitization at 20 wt.% Fe(NO₃)₃ thus provides an effective and sustainable route for producing high-quality rGO from renewable biomass resources, with promising implications for energy storage and advanced functional material applications.